Conceptualization of blockchain enabled interconnected smart microgrids. (October 2022) - Dinesha, Disha L.; Balachandra, P.
Abstract: Power systems are undergoing rapid transitions to incorporate renewable sources of generation and to combat climate change. The next stage of transitions will lead to a shift from large-scale, centralized systems to networks of small-sized, distributed electricity systems, which require distributed or decentralized ledgers for database management for efficient transactions. Distributed Ledger Technology (DLT) are a form of decentralized ledgers where the transactions (energy, information, and money) among various entities are maintained. One such DLT is blockchain technology which offers several advantages. Data recorded in blockchains are difficult to tamper with; have privacy protection; facilitate fast, accurate, and real-time settlement of financial transactions. Contemporary research has started focusing on their possible applications in energy systems. State-of-the-art suggests that while business and market aspects have been extensively discussed, the electrical constraints and implementation methodologies have not been adequately addressed. Furthermore, all the reviewed projects have implemented only peer-to-peer transactions that are not scalable. To incorporate the new entities like prosumers, inter-microgrid transactions, and interactions with the legacy power grid, new structural and operational frameworks are necessary. The proposed research explores the possibility of developing blockchain enabled smart microgrids (BSMG) with the above frameworks. It aims to build a conceptual framework of BSMG, including the transaction protocols and process flows. It proposes the inclusion of network constraints in a three-level transaction setup executed over a four-layered architecture. Another practical challenge is that BSMGs may be set up on different blockchain platforms. Hence, this paper also proposes implementing Inter-Blockchain Protocol for the first time to include interoperability and communication between different platforms. Finally, the performance metrics that will be used to validate the BSMGs are outlined. Highlights: Blockchain Enabled Smart Microgrids will play a pivotal role in Energy industry. Architecture is simplified to four distinct layers based on their functionality. Process flow modified to take electrical constraints into account. InterBlockchain Communication Protocol between microgrids proposed for first time. Qualitative and quantitative benchmarking measures to validate developed models.